The North East Adriatic Region: Territorial Cooperation and the Role of Planning Systems and Cultures - Marcks, Jakob; Knieling, Jörg; Vladova, Galya (European Spatial Research and Policy, 2017)
The aim of this paper is to map the spatial variations in the size of the shadow economy within Brussels. Reporting data provided by the National Bank of Belgium on the deposit of high denomination banknotes across bank branches in the 19 municipalities of the Brussels-Capital Region, the finding is that the shadow economy is concentrated in wealthier populations and not in deprived or immigrant communities. The outcome is a call to transcend the association of the shadow economy with marginalized groups and the wider adoption of this indirect method when measuring spatial variations in the shadow economy.